Executive Compensation and Ethnic Minority Status. Issue 3 (8th June 2017) - Guest, Paul M.
Abstract : We examine the compensation of ethnic minority executives in listed U.S. firms. The total pay of African American executives is 9 percent lower than that earned by Caucasians. This is due to lower base salary, lower bonus, and lower restricted stock grants. The lower bonus is due to a lower sensitivity to above‐average firm performance. African Americans also earn significantly less on the exercise of stock options, increasing the pay gap to 17 percent for total ex‐post pay. In contrast to African Americans, the compensation of Hispanic and Asian executives is comparable to Caucasians.